Development of Stir-Fried Chili Paste from Plasom Pla-nil (Fermented Tilapia) - Tayeh, Nutchanet; Sukjantra , Jariya; Na Nakorn , Kuenchan; Kamaelae, Rusnee (YRU Journal of Science and Technology, 2022)
The objective of this research was to develop stir-fried chili paste from Plasom Pla-nil (Fermented tilapia) for Ban Santi 2 Community, Mae Wad Sub-district, Tanto District, Yala Province by using Pla Som as a raw material in the production of chili paste to add value and variety to the product. Physico-chemical composition, microbial analysis, consumer acceptance, and nutritional product value were evaluated. The results showed that the suitable formula was Pickled Fish, fried garlic, red onion, dried bell pepper, dried hot pepper, sugar, and salt at 50.65%, 14.44%, 14.44%, 2.43%, 1.42%, 15.20%, and 1.42%, respectively. The product received the highest sensory evaluation score of all tasks (p<0.05). The product has pH values, moisture content, ash, brightness (L*), redness (a*), yellowness (b*) and free water content (aw) were 4.48±0.21 14.32±0.12 6.66±0.23 36.11±0.58 18.98±0.32 26.41±0.380 and 0.34±0.00, respectively. The studying of nutritional data revealed that the nutritional value of fish chili paste product (6 grams) per serving equals 30 kcal of energy, 1 g of fat, 10 mg of cholesterol, 1 g of protein, 4 g of carbohydrates, 2 g of sugar and 170 mg of sodium. The microbial quality test found that the stir-fried chili paste from pickled fish can be stored for 14 days at room temperature, with the microbial count meeting the Community Standards (TPS.130/2013 and TPS.321/2013). Stir-fried chili paste products received average consumer acceptance scores at the moderate to a very satisfy level of 76%